Testing The Indonesian Stock Market Arbitrage Pricing Model - Wawan Ichwanudin; Roni Kambara; Fauzi Sanusi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
This research aims to explain the return and risk premium using an APT model from the Indonesian stock market. The study uses a two-stage regression model. This study uses a sample of stocks included in the Kompas100 index. The stocks included in Kompas100 represent the market capitalization value from the Indonesian stock market. The originality of this research is the inclusion of foreign macro-factors and the use of surprise or unanticipated factors in the Pre-specified Macro-economic Arbitrage Pricing Theory Model. The results prove that there is a multi-factor APT model consisting of The risk premium for inflation, the risk premium for interest rates, and the risk premium for foreign macroeconomic factors represented by the Dow Jones index and the Shanghai index. The results of this study further strengthen the theory and previous research on the multi-factor APT model.